2022
DOI: 10.1371/journal.pntd.0010175
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose-derived stem cells ameliorates Echinococcus multilocularis-induced liver fibrosis in mice

Abstract: Background Alveolar echinococcosis (AE) can cause severe liver fibrosis and could be fatal if left untreated. Currently, there are no effective therapeutic options for AE-induced liver fibrosis. In view of the therapeutic potential of adipose-derived stem cells (ADSCs), we investigated whether ADSCs transplantation has the ability to control or reverse fibrosis progression in the liver of Echinococcus multilocularis (E. multilocularis) infected mice. Methodology/Principal findings C57BL/6 mice infected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…2 D). This is consistent with studies in other organs, where increased TGF-β receptor expression was observed in damaged liver tissue, and its suppression reduced liver damage in mice 39 . Furthermore, TGF-β signaling increases its receptor expression on the cell surface, as well as enhances its own signaling responses, indicating the complex biological interactions between TGF-β and TGF-β receptors.…”
Section: Discussionsupporting
confidence: 92%
“…2 D). This is consistent with studies in other organs, where increased TGF-β receptor expression was observed in damaged liver tissue, and its suppression reduced liver damage in mice 39 . Furthermore, TGF-β signaling increases its receptor expression on the cell surface, as well as enhances its own signaling responses, indicating the complex biological interactions between TGF-β and TGF-β receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Genome study indicated that E. multilocularis possesses TGF-β1, MAPK and Akt signaling pathways (Tsai et al, 2013;Zheng et al, 2013), beyond that, strong evidence suggest that during echinococccosis, the impaired host immune response is paralleled by an increased expression of TGF-β1 signaling components in periparasitic host cells and tissues (Nono et al, 2020). A later study on AE transplant treatment showed that through modulating the activity level of the TGF-β/Smad7 signaling pathway, liver fibrosis induced by E. multilocularis infection can be alleviated (Yang et al, 2022). In the present study, we observed apoptotic bodies in E. multilocularis PSC after treatment with PAB in vitro, referring apoptosis might be triggered.…”
Section: Groupsupporting
confidence: 56%
“… 545 ADSCs alleviated liver fibrosis in NASH mice by suppressing IL-17-mediated inflammation. 546 , 547 …”
Section: Novel Signaling Pathways and Pharmacological Targetsmentioning
confidence: 99%